AB1065 A Regional Audit of Joint Aspirates from Hot, Swollen Joints; Experiences in Northern Ireland. (10th June 2014) - Aston, K.; Savage, E.; Pathiraja, M.; Millar, A.; Stewart, R.; Ong, G.; Pendleton, A.
Abstract : Background: Hot, swollen joints are a common presenting complaint to health services. Prompt recognition of septic arthrtis is necessary. Untreated it can lead to loss of joint function or death, with a case fatality of 11% 1 . Other causes of hot, swollen joints must be recognised so correct management can be implemented and unnecessary treatment with antibiotics limited. Objectives: Objectives were to establish the prevalence of joint sepsis, examine causative organisms, and determine demographic variability. Other objectives were to determine risk factors for sepsis and review current practice regarding treatment. We aimed to determine if delay in transport and processing had an impact on diagnosis and treatment in peripheral hospitals. Methods: All joint aspirate samples sent to laboratories in Northern Ireland over 6 months were analysed (1/10/2011 – 27/3/2012). Sites included 2 central hospitals and 5 district general hospitals. Aspirates involving a prosthetic joint and those received from general practice were excluded. Clinical information was gathered retrospectively from patient notes. Results: Samples from 259 patients were analysed. Septic arthritis was initially suspected in 74 patients but only 27 (10.4%) had a final diagnosis of septic arthritis. In 47 (18.1%) antibiotics were discontinued after culture was negative. Crystal arthritis was the final diagnosis in 39 of these patients. In cases of suspected septic joint only 20.3% had simultaneous blood cultures sent. 25 (9.7%) of suspected cases were given antibiotics prior to joint aspiration. 87 (33.6%) were diagnosed with crystal arthritis. 105 (40.5%) were given an alternative diagnosis including; inflammatory arthritis, osteoarthritis, haemarthrosis and reactive arthritis. Clinical information was not available for the remainder. Pathogens isolated from aspirates included; MSSA (46%), streptococci (21%), pseudomonas (8%) and MRSA (4%). 21% were culture negative (50% of these had antibiotics before joint aspiration) Results showed demographic variability with gram negative bacteria cultured from samples from the Belfast Trust only. One case of MRSA was documented in the Western Trust. Empiric antibiotic choice was found to be appropriate in all. 77% of samples were received by the laboratory within 24 hours of collection. Risk factors for septic joint included; diabetes, osteoarthritis, inflammatory joint disease and oral steroids. No cases of joint sepsis were associated with intra-articular steroid injections. An estimated 220 intra-articular injections are carried out per week within the province. There were no cases of joint sepsis in patients on biologic treatment. Conclusions: Sepsis was shown to be the cause of the hot, swollen joint in 10.4% of joint aspirations. In suspected septic athritis 34% received antibiotics prior to aspiration. This may unfortunately mar the clinical picture. Crystal arthropathies make up the majority of aspirates sent for analysis, secondary to an acutely swollen. References: Coekley et al. BSR&BHPR, BOA, RCGP and BSAC guidelines for the management of the hot swollen joint in adults. Weston V C et al. Clinical features and outcomes of septic arthritis in a single UK health district 1982-1991. Ann Rheum Dis 1999;58:214-219 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2251